2021
DOI: 10.1088/1361-6420/ac3f81
|View full text |Cite
|
Sign up to set email alerts
|

Γ -convergence of Onsager–Machlup functionals: I. With applications to maximum a posteriori estimation in Bayesian inverse problems

Abstract: The Bayesian solution to a statistical inverse problem can be summarised by a mode of the posterior distribution, i.e. a maximum a posteriori (MAP) estimator. The MAP estimator essentially coincides with the (regularised) variational solution to the inverse problem, seen as minimisation of the Onsager–Machlup (OM) functional of the posterior measure. An open problem in the stability analysis of inverse problems is to establish a relationship between the convergence properties of solutions obtained by the varia… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 30 publications
1
12
0
Order By: Relevance
“…The next result states this equivalence between OM minimisers and weak modes under the M-property and shows that the M-property is inherited by a posterior of the form (1.1) from the prior. This generalises proposition 4.1 and lemma B.8 of Ayanbayev et al (2022a) to potentials that are merely continuous rather than locally uniformly continuous. In the specific case that µ 0 is a Gaussian measure on a separable Banach space X, the claim (a) generalises theorem 3.2 of Dashti et al (2013), which requires that the potential is locally bounded and Lipschitz.…”
Section: Definition 25 (M-property)supporting
confidence: 68%
See 2 more Smart Citations
“…The next result states this equivalence between OM minimisers and weak modes under the M-property and shows that the M-property is inherited by a posterior of the form (1.1) from the prior. This generalises proposition 4.1 and lemma B.8 of Ayanbayev et al (2022a) to potentials that are merely continuous rather than locally uniformly continuous. In the specific case that µ 0 is a Gaussian measure on a separable Banach space X, the claim (a) generalises theorem 3.2 of Dashti et al (2013), which requires that the potential is locally bounded and Lipschitz.…”
Section: Definition 25 (M-property)supporting
confidence: 68%
“…Strong modes were proposed by Dashti et al (2013), and weak modes were later suggested by Helin and Burger (2015) as a more convenient definition when connecting MAP estimators with variational solutions to inverse problems. Following Ayanbayev et al (2022a), we consider only global weak modes in this article.…”
Section: Mode Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…Agapiou et al (2018) studied the MAP estimator for Bayesian inversion with sparsity-promoting Besov priors. The connection between weak and strong modes was further explored in Lie and Sullivan (2018), and Ayanbayev et al (2021a, 2021b discussed stability and convergence of global weak modes using Γ-convergence. Recently, Lambley and Sullivan (2022) presented a perspective on modes via order theory.…”
Section: Related Workmentioning
confidence: 99%
“…Therefore, the novelty of theorem 1 is not in the proof that the cost functions converge, but that the randomized cost functions yield solutions that asymptotically converge to the solution of the non-randomized cost function. While we constructively prove Γ−convergence for (4), our result follows immediately under the much stronger assumption that the prior term already exhibits Γ−convergence and the likelihood term converges continuously based on the results presented in Ayanbayev et al (2021). In fact, the cost functions themselves do not converge as there is an additional bias term in expected value of the randomized cost function, J , compared to the deterministic cost function, J .…”
Section: Asymptotic Convergence Analysis For Inverse Problemsmentioning
confidence: 53%